Stormwater biofilter response to high nitrogen loading under transient flow conditions: Ammonium and nitrate fates, and nitrous oxide emissions. (15th February 2023) - Feraud, Marina; Ahearn, Sean P.; Parker, Emily A.; Avasarala, Sumant; Rugh, Megyn B.; Hung, Wei-Cheng; Li, Dong; Werfhorst, Laurie C. Van De; Kefela, Timnit; Hemati, Azadeh; Mehring, Andrew S.; Cao, Yiping; et al.
Highlights: N export from full-scale biofilters studied for successive transient flow storms. Soil N was mineralized, and inflow NH4 + nitrified, during antecedent dry periods. Low N2 O emissions or denitrification, with high NO3 − leaching during storms. Denitrifying genes were abundant, but potential denitrifying enzyme activity low. Results consistent for chemical, enzymatic, biological, and stable isotope data. Abstract: Nitrogen (N) in urban runoff is often treated with green infrastructure including biofilters. However, N fates across biofilters are insufficiently understood because prior studies emphasize low N loading under laboratory conditions, or use "steady-state" flow regimes over short time scales. Here, we tested field scale biofilter N fates during simulated storms delivering realistic transient flows with high N loading. Biofilter outflow ammonium (NH4 + -N) was 60.7 to 92.3% lower than that of the inflow. Yet the characteristic times for nitrification (days to weeks) and denitrification (days) relative to N residence times (7 to 30 h) suggested low N transformation across the biofilters. Still, across 7 successive storms, total outflow nitrate (NO3 − -N) greatly exceeded (3100 to 3900%) inflow nitrate, a result only explainable by biofilter soil N nitrification occurring between storms. Archaeal, and bacterial amo A gene copies (2.1 × 10 5 to 1.2 × 10 6 gc g soil −1 ), nitrifier presence by16S rRNA gene sequencing, and outflow δ 18 O-NO3 − values (-3.0 to 17.1 ‰) reinforced that nitrification was occurring. A ratio of δ 18 O-NO 3− to δ 15 N-NO3 − of 1.83 for soil eluates indicated additional processes: N assimilation, and N mineralization. Denitrification potential was suggested by enzyme activities and soil denitrifying gene copies ( nir K + nir S: 3.0 × 10 6 to 1.8 × 10 7 ; nos Z: 5.0 × 10 5 to 2.2 × 10 6 gc g soil −1 ). However, nitrous oxide (N2 O-N) emissions (13.5 to 84.3 μg N m − 2 h − 1 ) and N2 O export (0.014 g N) were low, and soil nitrification enzyme activities (0.45 to 1.63 mg N kg soil −1 day −1 ) exceeded those for denitrification (0.17 to 0.49 mg N kg soil −1 day −1 ). Taken together, chemical, bacterial, and isotopic metrics evidenced that storm inflow NH4 + sorbs and, along with mineralized soil N, nitrifies during biofilter dry-down; little denitrification and associated N2 O emissions ensue, and thus subsequent storms export copious NO3 − -N. As such, pulsed pass-through biofilters require redesign to promote plant assimilation and/or denitrification of mineralized and nitrified N, to minimize NO3 − -N generation and export. Graphical abstract: Image, graphical abstract